The Web Application Development for Selling Ready-to-cook Meal Kits: Tham-kin - Mainoy, Chonticha; Sae-ieb, Navarat (Journal of Science and Technology Songkhla Rajabhat University, 2022)
From the outbreak of the virus, human beings have to change many activities of their lifestyle. Including food, cleanliness and safety must be considered. The objectives of this study were to 1) to study problems in purchasing raw materials and cooking in the era of COVID-19 2) to study the design of web applications for web application development. for selling ready-to-cook meals and 3) assessing the effectiveness of a web application for selling ready-to-cook meals. The sample of this study is the population, Bangkok city and surrounding areas. There is a convenient random sampling method for 110 people. The research instrument was a questionnaire. Statistics used in the initial analysis These were descriptive statistics such as percentage frequency, Kano's model analysis, and customer satisfaction coefficient calculation. The results of a study of behaviors related to problems in purchasing ingredients and cooking in the era of the Covid-19 epidemic. It was found that the purchase of raw materials from the market caused excess raw materials. There is also interest in web applications for selling ready-to-cook meal kits to help you get the ingredients to fit your individual meal needs. Therefore, the researcher has designed and developed a web application for selling ready-to-cook meal kits for use in allocating tableware from the price, amount of food, food types to meet the needs of the user group. From the assessment of satisfaction with the functions and the overall picture of the developed web application, it was found that the sample of users had the highest average level of satisfaction. ( = 4.52, SD = 0.65)